2017
DOI: 10.1186/s13071-017-2507-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium reichenowi EBA-140 merozoite ligand binds to glycophorin D on chimpanzee red blood cells, shedding new light on origins of Plasmodium falciparum

Abstract: BackgroundAll symptoms of malaria are caused by the intraerythrocytic proliferation of Plasmodium merozoites. Merozoites invade erythrocytes using multiple binding ligands that recognise specific surface receptors. It has been suggested that adaptation of Plasmodium parasites to infect specific hosts is driven by changes in genes encoding Plasmodium erythrocyte-binding ligands (EBL) and reticulocyte-binding ligands (RBL). Homologs of both EBL and RBL, including the EBA-140 merozoite ligand, have been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The identity of the recognized sialoprotein also differs between P. reichenowi and P. falciparum. While Pf EBA-140 binds to glycophorin C as described above, the P. reichenowi homolog interacts with glycophorin D (Zerka et al, 2017). These observations favor a model in which humans and P. falciparum co-evolved and P. falciparum's ability to preferentially recognize Neu5Accontaining proteins led to its emergence as the most deadly human parasite (Martin et al, 2005;Proto et al, 2019).…”
Section: Sialic-acid-containing Glycansmentioning
confidence: 92%
“…The identity of the recognized sialoprotein also differs between P. reichenowi and P. falciparum. While Pf EBA-140 binds to glycophorin C as described above, the P. reichenowi homolog interacts with glycophorin D (Zerka et al, 2017). These observations favor a model in which humans and P. falciparum co-evolved and P. falciparum's ability to preferentially recognize Neu5Accontaining proteins led to its emergence as the most deadly human parasite (Martin et al, 2005;Proto et al, 2019).…”
Section: Sialic-acid-containing Glycansmentioning
confidence: 92%
“…The glycophorin D (a truncated form of GPC) was identified as receptor for P . reichenowi EBA-140 ligand [ 60 ] ( Figure 2 ).…”
Section: Sialic Acidsmentioning
confidence: 99%
“…The ape homologues of the EBA P. falciparum ligands, including chimpanzee P . reichenowi , have been identified [ 60 , 62 ]. It was shown that the receptors for P .…”
Section: Sialic Acidsmentioning
confidence: 99%
“…As discussed above, there is a general agreement that GPC but not GPD is P. falciparum EBA-140 receptor on human RBCs [79, 8183, 97, 98]. However, evaluation of the binding of the homologous P. reichenowi EBA-140 ligand binding to chimpanzee RBCs [99] unexpectedly demonstrated that the chimpanzee homolog of human GPD is probably the receptor for that ligand [4, 100]. It may be hypothesized that GPD is an ancestral EBA-140 receptor in non-human primates, while GPC emerged as a new receptor for P. falciparum in humans.…”
Section: Introductionmentioning
confidence: 99%